2020
DOI: 10.1186/s41687-020-00239-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of socio-cultural factors and environmental resources on the health related quality of life of children and adolescents after congenital heart disease surgery: parental perspectives from a low middle income country

Abstract: Background: Health related quality of life (HRQOL) is an important indicator of long-term well-being, influenced by environmental factors such as family, culture, societal norms and available resources. This study aimed to explore parental perspectives on the influence of socio-cultural factors and environmental resources on the HRQOL of children and adolescents after congenital heart disease (CHD) surgery. Methods: Using a descriptive, qualitative design, semi-structured interviews of children/adolescents who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…At the same time, the quality of life is also affected by social and parental factors. The prognosis of children with a family income that can afford good treatment conditions and provide good nutritional conditions and a comfortable and safe living environment is better [ 22 , 23 ]. Access to good social health maintenance services is also an important factor in improving the quality of life of children after surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the quality of life is also affected by social and parental factors. The prognosis of children with a family income that can afford good treatment conditions and provide good nutritional conditions and a comfortable and safe living environment is better [ 22 , 23 ]. Access to good social health maintenance services is also an important factor in improving the quality of life of children after surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac surgery types include coronary artery bypass grafting (CABG), repair or removal of the heart valve, heart transplant, and installation of machines or artificial hearts for ventricular assistance (Stigler Granados et al, 2019). So, health-related quality of life (HRQOL) is a significant indicator of long-term well-being, influenced by environmental factors such as family, culture, community norms, and available resources that better and earlier diagnostics and clinical management of congenital heart disease (CHD) have led to decreased mortality and increased achieved outcomes (Ladak et al, 2020).…”
Section: Justification Of the Problemmentioning
confidence: 99%
“…So, health‐related quality of life (HRQOL) is a significant indicator of long‐term well‐being, influenced by environmental factors such as family, culture, community norms, and available resources that better and earlier diagnostics and clinical management of congenital heart disease (CHD) have led to decreased mortality and increased achieved outcomes (Ladak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to Rosmarin et al (2011), a worldview based on trust in God can mitigate negative appraisals of adversity, in addition to contributing to positive religious coping and serving as a spiritual resource in the face of stressful life events. Indeed, other authors have also shown how trust in God can be a powerful religious and spiritual coping strategy (Burns 2004;Büssing et al 2021;Ladak et al 2020). In contrast, mistrust in God seems to measure the notion that God is willfully ignorant and malevolent, and is related to divine spiritual struggles, which reflect the tension between the individual and God (Rosmarin et al 2009b).…”
Section: Trust and Mistrust In Godmentioning
confidence: 99%